Acesso aos cuidados primários de saúde: Revisão integrativa - Rocha, Suelen Alves [UNESP]; Bocchi, Silvia Cristina Mangini; de Godoy, Moacir Fernandes [UNESP] (FapUNIFESP (SciELO), 2016)
Timely access to primary health care is still a problem in many countries. We conducted a literature integrative review aimed to analyze the national and international scientific production about the increase of access in primary health care. The analysis brought out 16 articles published between 2009 and 2014, in the databases LILACS, SciELO, PubMed and Scopus. Most publications were available in journals of primary health care and in English. Several methodological approaches were adopted, with a predominance of observational epidemiological designs. An equitable health system provides timely access and continuity of care. This article presents the main strategies to reach both guidelines. The advanced access appears the most promising scheduling model because balances the demand and capacity while controlling delay. However, it is no use to modify the scheduling model without providing the necessary infrastructure to maintain it.
Access to primary health care: Integrative review
Keywords: Access to health services; Aged; Family Health Strategy; Primary health care